Visual Exploration in Autism Spectrum Disorder: Exploring Age Differences and Dynamic Features Using Recurrence Quantification Analysis. Issue 11 (1st October 2018) - Manyakov, Nikolay V.; Bangerter, Abigail; Chatterjee, Meenakshi; Mason, Luke; Ness, Seth; Lewin, David; Skalkin, Andrew; Boice, Matthew; Goodwin, Matthew S.; Dawson, Geraldine; Hendren, Robert; Leventhal, Bennett; et al.
Abstract : Eye‐tracking studies have demonstrated that individuals with autism spectrum disorder sometimes show differences in attention and gaze patterns. This includes preference for certain nonsocial objects, heightened attention to detail, and more difficulty with attention shifting and disengagement, which may be associated with restricted and repetitive behaviors. This study utilized a visual exploration task and replicates findings of reduced number of objects explored and increased fixation duration on high autism interest objects in a large sample of individuals with autism spectrum disorder ( n = 129, age 6–54 years) in comparison with a typically developing group. These findings correlated with parent‐reported repetitive behaviors. Additionally, we applied recurrent quantification analysis to enable identification of new eye‐tracking features, which accounted for temporal and spatial differences in viewing patterns. These new features were found to discriminate between autism spectrum disorder and typically developing groups and were correlated with parent‐reported repetitive behaviors. Original and novel eye‐tracking features identified by recurrent quantification analysis differed in their relationships to reported behaviors and were dependent on age.Trial Registration: NCT02299700. Autism Research 2018, 11: 1554–1566 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Using eye‐tracking technology and a visual exploration task, we showed that people with autism spectrum disorder (ASD) spend more time looking at particular kinds of objects, like trains and clocks, and look at fewer objects overall than people without ASD. Where people look and the order in which they look at objects were related to the restricted and repetitive behaviors reported by parents. Eye‐tracking may be a useful addition to parent reports for measuring changes in behavior in individuals with ASD.